استفاده از مدل برنامه‌ریزی خطی مختلط عدد صحیح جهت بهینه-سازی زاویه و شدت پرتو در پرتودرمانی با شدت مدوله شده - صادقیه, احمد; سواری, مریم; نیک فرجام, ابوالفضل (Journal of Shaheed Sadoughi University of Medical Sciences & Health Services, 2018)
Introdution: Intensity- modulated radiation therapy is one of the treatment methods for cancer tumors. The effectiveness of this method is dependent on the accuracy and treatment planning quality. Therefore, there is a need for a plan to select the angle and intensity simultaneous optimum of radiation. Methods: In this study, an mixed integer linear programming model was proposed for simultaneous optimization of angles and intensity in the GAMS programming environment.To implement the model, after the patient's CT was prepared, the organ cantoring was performed by CERR software and the Influence Matrix was obtained for each organ. After collecting the inputs of the problem, in order to obtain the desired outputs, was used from The GAMS software from the CPLEX solver. Results: Finally, the actual case of head and neck cancer is analyzed to demonstrate the effectiveness of the model. From the angle of the candidate, ̅ ، is chosen as the optimal radiation angles. The maximum dose received by the brainstem was 3. 999, Mandible 70, LeftOrbit 0.026, RightOrbit 0.440, Parotid Gland 0.881, OpticChiasm 0.177, OpticNerves 0.167, spinalcord 9.929 Gray and the minimum dose received by the tumor is 70 Gray. Also, the optimal amount of intensity for implementing the treatment plan on the patient is achieved. Conclusion: The dose received by each organ was significantly improved compared to prescribing doses. Similarly, the comparison of the Dose Volume Histogram obtained by solving a common problem with the model and software CERR, Represents the optimal performance of the model, which improves the security rate and reduces the cost for healthy tissues.